New oxindole alkaloids with selective osteoclast inhibitory activity from Gelsemium elegans. Issue 10 (23rd May 2022) - Wei, Xin; Huang, Xiao-Teng; Zhang, Li-Yan; Hu, Xin-Yue; Zhang, Wei; Zhou, Yong-Qiang; Yu, Hao-Fei; Ding, Cai-Feng; Zhang, Lan-Chun; Liu, Xia; Zhou, Ying
Abstract: A new alkaloid 14-hydroxygelseziridine (1 ), along with four known oxindoles (2-5 ), was isolated and characterized from the well-known toxic medicine Gelsemium elegans . Their structures were elucidated by means of spectroscopic techniques and quantum chemistry calculations. Structurally, new compound 1 has a three membered oxygen ring at N -4/C-20. All compounds were tested for osteoclast (MOC-1) inhibitory activity in vitro . Compound 2 exhibited the selective osteoclast inhibitory activity. Flow cytometry revealed that the apoptosis of osteoclasts induced by 2 . Furthermore, the PCR bioassay suggested that compound 2 may activate the apoptotic pathway of osteoclasts by reducing the expression of IL-6 and c-Jun, and increasing caspase 9. This work provided the evidence for the rationality as the traditional treatment for bone related diseases of G. elegans, and shed a new light on its further research. Graphical Abstract: UF0001